2017
DOI: 10.1051/0004-6361/201730915
|View full text |Cite
|
Sign up to set email alerts
|

Seismology of contracting and expanding coronal loops using damping of kink oscillations by mode coupling

Abstract: Aims. We extend recently developed seismological methods to analyse oscillating loops which feature a large initial shift in the equilibrium position and investigate additional observational signatures related to the loop environment and oscillation driver. Methods. We model the motion of coronal loops as a kink oscillation damped by mode coupling, accounting for any change in loop length and the possible presence of parallel harmonics in addition to the fundamental mode. We apply our model to a loop which rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 75 publications
(110 reference statements)
2
36
0
1
Order By: Relevance
“…More recently Pascoe et al (2016a) used AIA/SDO observations to spatially resolve the fundamental and second harmonic, justifying their interpretation by invoking the ratio of oscillation periods, the spatial dependence of the amplitudes for each mode, and anti-phase oscillations of the loop legs for the second harmonic. Seismological studies by Pascoe et al (2017a) and Pascoe et al (2017b) found evidence of higher (second and/or third) harmonics in all cases of kink oscillations excited by external perturbations, consistent with the numerical simulations by Pascoe et al (2009), but noticeably absent in the case of a kink oscillation generated by the post-flare implosion studied by Russell et al (2015). In these and all previous cases of detection of multiple harmonics, the oscillation decayed rapidly.…”
Section: Introductionsupporting
confidence: 83%
“…More recently Pascoe et al (2016a) used AIA/SDO observations to spatially resolve the fundamental and second harmonic, justifying their interpretation by invoking the ratio of oscillation periods, the spatial dependence of the amplitudes for each mode, and anti-phase oscillations of the loop legs for the second harmonic. Seismological studies by Pascoe et al (2017a) and Pascoe et al (2017b) found evidence of higher (second and/or third) harmonics in all cases of kink oscillations excited by external perturbations, consistent with the numerical simulations by Pascoe et al (2009), but noticeably absent in the case of a kink oscillation generated by the post-flare implosion studied by Russell et al (2015). In these and all previous cases of detection of multiple harmonics, the oscillation decayed rapidly.…”
Section: Introductionsupporting
confidence: 83%
“…The seismological method is based on the use of the kink oscillation damping profile as described in Pascoe et al (2016bPascoe et al ( , 2017aPascoe et al ( , 2017c. Large-amplitude standing kink oscillations are typically observed for fewer than six cycles (e.g., Figure 2 of .…”
Section: Seismology Using Damped Kink Oscillationsmentioning
confidence: 99%
“…They are commonly used to infer the strength of the coronal magnetic field (e.g., Nakariakov et al 1999;Nakariakov & Ofman 2001;Van Doorsselaere et al 2008;White & Verwichte 2012;Pascoe et al 2016b;Sarkar et al 2016). Additional structuring information may be obtained using higher harmonics, which there is increasing evidence of (e.g., Verwichte et al 2004;De Moortel & Brady 2007;Van Doorsselaere et al 2007;Wang et al 2008;Srivastava et al 2013;Pascoe et al 2016aPascoe et al , 2017aPascoe et al , 2017cLi et al 2017). The strong damping of kink oscillations is attributed to resonant absorption (Sedláček 1971), which requires a smooth transition between the high-density plasma inside coronal loops and the background plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason multi-mode observations would be particularly informative. Observations of standing kink oscillations have recently been used to calculate the density (and Alfvén speed) profiles for coronal loops using their damping profiles by resonant absorption (Pascoe et al 2013a(Pascoe et al , 2016(Pascoe et al , 2017a(Pascoe et al , 2017c. The perpendicular inhomogeneity size has also been independently estimated by forward modeling the EUV intensity (Goddard et al 2017;Pascoe et al 2017b), although so far this has relied on the isothermal approximation (e.g., Aschwanden et al 2007), whereas hot (multi-thermal) flaring loops may require more sophisticated forward modeling (e.g., De Moortel & Bradshaw 2008;Van Doorsselaere et al 2016a).…”
mentioning
confidence: 99%